CPT-Based Multi-Objective Strategy for Power Quality Enhancement in Three-Phase Three-Wire Systems under Distorted and Unbalanced Voltage Conditions - Paredes, Helmo K. Morales [UNESP]; Rodrigues, Diego T. [UNESP]; Cebrian, Juan C. [UNESP]; Bonaldo, Jakson P. (Institute of Electrical and Electronics Engineers (IEEE), 2021)
This paper explores the application of multifunctional inverters connected to the electrical network, to propose an adaptable system to individually control reactive power, load imbalance, and harmonic currents. Based on Conservative Power Theory (CPT), the dynamic compensation of Power Quality (PQ) indices is carried out under different conditions of demand and energy generation. First, a set of global factors for reactive power, imbalances, and current harmonics is introduced, which are effective even for bidirectional power flows in systems with harmonic voltage distortion and/or voltage unbalance. This set of factors gives rise to a multiobjective decision-making algorithm to estimate coefficients of proportionality, which instantly considers the reference signals linked to the disturbances, enabling to individually keep track of the target values of each of the PQ indices, as customarily established through standards or electricity utility criteria. As a result, this proposed approach allows a multiobjective operation of the inverter connected to the network, thereby allowing maximum use of energy generated, as well as limiting energy losses of distribution networks, and enhancement of the PQ of a prosumer. Finally, to illustrate the effectiveness of the proposed approach, different case studies were simulated with this set of case studies, including one representative real case containing a PV system connected to the network and a non-linear unbalanced load with variable demand.
Keywords: Active filters; bidirectional power flow; distributed energy resources; grid-connected inverters; industrial power systems; power conditioning; power quality